Prevalence of nutritional anemia and its risk factors in children under five in the Gaza Strip - El Bilbeisi, Abdel Hamid (Frontiers in Nutrition, 2025)
BackgroundThe present study aimed to determine the prevalence of anemia and its associated risk factors among under-five children aged 24–59 months in Gaza Strip, Palestine.MethodThis cross-sectional study was conducted in 2023 before Gaza war, among a representative sample of under-five children. A total of 750 children, aged 24–59 months, were selected from all Gaza Strip governorates, using a cluster random sampling method. Children and their parents were assessed using an interview-based questionnaire, anthropometric measurements, biochemical measurements, and clinical examination. Statistical analysis was performed using SPSS version 25.ResultsThe prevalence of anemia (Hb <11 g/dL) among under-five children was 35.6%. Of them, 77.5% had mild anemia and 22.5% had moderate anemia. The prevalence of iron deficiency anemia (IDA) (Hb <11 g/dL and SF <12 μg/L) among under-five children was 4.0%. Various risk factors were found to be statistically significant in relation to nutritional anemia. These included child-related factors such as age, weight, height, sibling arrangement, governorate, and place of residence. Family characteristics like the father’s age, smoking habits, the mother’s education, employment, marital history, income, housing ownership, and a history of anemia during pregnancy also played a role. Additionally, dietary factors such as tea, meat, crisps, cola, fruits, breastfeeding practices, malnutrition, appetite, and hereditary diseases were significantly associated with anemia in these children (p-values <0.05 for all).ConclusionOur study clearly demonstrates that anemia is highly prevalent (35.6% anemia, and 4.0% IDA) among under-five children in Gaza Strip governorates. Different risk factors including the child’s and family characteristics, and the consumption of some of food items were associated with a high prevalence of anemia. The high prevalence of anemia should be seriously considered and policy makers should take steps to reduce it.